Ureterocystoplasty in a Girl with Bilateral Ureterovesical Junction Obstructions and Small Bladder Capacity: The First Case Report of Thailand - Chaiyong Nualyong; Bansithi Chaiyaprasithi; Thawathai Mankongsrisuk; Santosh Shrestha; Kittipong Phinthusophon (Siriraj Medical Journal, 2018)
Objective: Ureterocystoplasty is one of the treatment options for small bladder capacity with hydroureter. To the best of our knowledge, there was no report of a patient who underwent this procedure in Thailand. Case presentation: A 4-year-old girl, who presented with obstructive anuria at birth was diagnosed with bilateral ureteropelvic junction obstruction and small bladder capacity. At the age of 2 years old, she underwent a teapot ureterocystoplasty with left to right transuretero-ureterostomy with right ureteral reimplantation. Postoperative complication was observed. The bladder capacity was evaluated and kidney ultrasonography was done during the follow up. There was no complication during the perioperative period. The bladder capacity was increased from 25 ml to 240 mL in 2 years postoperatively. Both kidneys also showed the decrease in degree of hydronephrosis. Conclusion: Ureterocystoplasty is a favorable treatment option for the patients with small bladder capacity and marked hydroureter. The procedure itself is not difficult to perform. Moreover, there are no mucous related complications and metabolic disturbances.